Fabrication of Porous Silicon Carbide Ceramics with High Electromagnetic Interference Shielding Effectiveness. Issue 34 (4th December 2017) - Liu, Chenyu; Qiu, Zechao; Yu, Dawei; Kirk, Donald W.; Xu, Yongjun
Abstract: Porous SiC ceramics were synthesized for its potential electromagnetic interference (EMI) shielding application, with the utilization of a biomass material as the porous template and carbon precursor. A silicon infiltration process was conducted in the temperature range of 1400–1600 °C with the absence of any catalyst to produce the porous SiC ceramics. The porous SiC ceramics were characterized using scanning electron microscope, X‐ray diffraction and microwave vector network analyses. It was found that significantly higher EMI shielding effectiveness can be achieved using a higher silicon infiltration temperature. The porous SiC ceramics synthesized at 1600 °C possess the highest shielding value, reaching 60 dB at a high frequency range from 10 GHz to 18 GHz. It was proposed that the porous structure of the SiC can increase EM shielding performance by attenuating EM waves via multiple internal reflection and transmission of the incident and re‐reflected waves through the SiC walls of the porous network. Abstract : Porous SiC ceramics were synthesized for its potential electromagnetic interference shielding application, with the utilization of a biomass material as porous template and carbon precursor. The porous SiC ceramics synthesized at 1600 °C possess the highest shielding value reaching 60 dB. It was proposed that the porous structure of the SiC can increase EMI shielding performance by attenuating EM waves via multiple internal reflection and transmission of the incident and re‐reflected waves through the SiC walls of the porous network.